Deus e o Diabo na Alcova: uma leitura do sonetário de Glauco Mattoso em busca das presenças poéticas de Deus e do Diabo - Lisboa, Emmanuel Gonçalves Guimarães (2010)
The following work treats about God's images in the contemporary poetry. Thereunto, we have selected Glauco Mattoso, a native of São Paulo poet who passes through several faces of the recent brazilian poetry. Of his vast production, we analyze, in this work, only the sonnets, without a cutting of composition or phase - we worry about the presence of God in his sonnets collection. To do so, we have read, written up and cataloged three thousand sonnets, and twenty-nine of them found the presence of God with real meaning to the content. However, we have analyzed carefully only a small part of these sonnets. For the analysis, we have anchored on the concepts of literary criticism coming from Iumna Maria Simon and Vinicius Dantas, the reflections of Hugo Friederich, and on sociological relationships of men with God studies, by Roger Bastide. The work is divided into three chapters. The first, "Um exercício de história" (A History Exercise), tries to situate the contemporary Brazilian poetry and insert Glauco Mattoso in this scenario. Also in this chapter, relevant and influential artists appear in Glauco's literary education and in the formation of pornographic and accursed tradition of portuguese language. The second chapter, "De onde vem e como vemos" (Whence it comes and how we see it), is the theoretical framework we use to read Glauco's poetry. Initially, we present Iumna Maria Simon's and Vinícius Dantas's theories, and then Hugo Friederich's. After that, these concepts are applied separately in some Glauco's poems with a distinct theme from the one we have investigated. Finally, we discuss the sociological categories defined by Roger Bastide. In the last chapter, the poems are analyzed following four different categories, but similar with regard to the theme. We ascertain the poems in it's interpretation about the divine figure, the poems in which God acts, or is claimed to act in the political, egocentric, and reversal horizons. Throughout the work, we try to understand the ways how the divine figure is treated in Glauco's poetry, and by extension, we try to point out the relations of man and God in today's society